Pembelajaran Teks Deskripsi Dalam Penerapan Kurikulum Merdeka di SMP Negeri 2 Singaraja - Zalukhu, Vista Murni; Sutama, I Made; Tantri, Ade Asih Susiari (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This qualitative descriptive is, (1) the planning of descriptive text learning in implementing the independent curriculum in class VII of SMP Negeri 2 Singaraja, (2) the implementation and evaluation of descriptive text learning in implementing the independent curriculum in class VII of SMP Negeri 2 Singaraja, 3) obstacles or obstacles faced by teachers and students in learning descriptive texts in implementing the independent curriculum in class VII of SMP Negeri 2 Singaraja. The subjects of this research are teachers and students. The object of the research is learning descriptive texts in implementing the independent curriculum. The methods used to collect research data are documentation, observation and interviews. The data analysis technique used carries out several stages, namely reduction, presentation, interpretation, and drawing conclusions. The results of this research show that; (1) descriptive text learning in implementing the independent curriculum in class VII of SMP Negeri 2 Singaraja has been well planned, (2) descriptive text learning in implementing the independent curriculum in class VII of SMP Negeri 2 Singaraja is still not implemented optimally (3) descriptive text learning In implementing the independent curriculum in class VII SMP Negeri 2 Singaraja there are still problems or obstacles for both teachers and students.